Improvement of intestinal barrier function, gut microbiota, and metabolic endotoxemia in type 2 diabetes rats by curcumin. Issue 2 (20th December 2021) - Huang, Jingze; Guan, Binbin; Lin, Lijing; Wang, Yanping
ABSTRACT: Type 2 diabetes mellitus (T2DM) is known as a complex genetic disease characterized by genetic and environmental factors. The imbalanced intestinal flora and intestinal mucosal barrier are considered to be related to T2DM. Curcumin has been proved to affect the progression of T2DM. T2DM animal was established by low-dose streptozotocin intraperitoneal injection combined with high-fat diet (HFD) feeding. Hematoxylin and eosin (HE) staining and transfer electron microscopy (TEM) were used to observe morphological changes of intestinal tissues of T2DM rats. Insulin and glucose tolerance tests were performed to investigate the influence of curcumin on blood glucose. Curcumin significantly improved the intestinal integrity, hyperglycemia and insulin resistance in diabetic rats. The metabolic endotoxemia induced by HFD in diabetic rats was inhibited remarkably. Curcumin reversed gut microbiota dysbiosis in diabetic rats caused by HFD. We demonstrated that curcumin could protect intestinal mucosal barrier, improve insulin resistance and reduce blood glucose in diabetic rats. This study might provide experimental evidence for the prevention and treatment in T2DM.